NMR of molecular endofullerenes dissolved in a nematic liquid crystal. Issue 19 (26th April 2017) - Kouřil, Karel; Wickens, Christopher; Meier, Benno; Alom, Shamim; Gräsvik, John; Whitby, Richard J.; Levitt, Malcolm H.
Abstract : We report the NMR of the molecular endofullerenes H2 @C60, H2 O@C60 and HF@C60 dissolved in the nematic liquid crystal N -(4-methoxybenzylidene)-4-butylaniline (MBBA). Abstract : We report the NMR of the molecular endofullerenes H2 @C60, H2 O@C60 and HF@C60 dissolved in the nematic liquid crystal N -(4-methoxybenzylidene)-4-butylaniline (MBBA). The 1 H NMR lines of H2 and H2 O display a doublet splitting due to residual dipole–dipole coupling. The dipolar splitting depends on temperature in the nematic phase and vanishes above the nematic–isotropic phase transition. The 19 F spectrum of HF@C60 dissolved in MBBA displays a doublet splitting in the nematic phase, with contributions from the 1 H– 19 F dipole–dipole coupling and J -coupling. The phenomena are analyzed using a model in which the fullerene cages acquire a geometrical distortion, either through interaction with the liquid crystal environment, or through their interaction with the endohedral molecules. The distorted cages become partially oriented with respect to the liquid crystal director, and the endohedral molecules become partially oriented with respect to the distorted cages.